2022
DOI: 10.35622/inudi.b.048
|View full text |Cite
|
Sign up to set email alerts
|

Gimnasia educativa básica

Abstract: El libro fue adecuado a partir de una investigación cuyo objetivo fue determinar el efecto de la aplicación del Programa DEPREPCEP en el aprendizaje de la Gimnasia Básica en niñas de la Liga de Gimnasia de Puno (Perú). El estudio fue experimental de tipo aplicativo, con un diseño de pre y post-test de un solo grupo. La población de estudio fue de 60 niñas y la muestra por 30 niñas de la Liga de Gimnasia de Puno. Para la recolección de datos se utilizó como instrumento la lista de Cotejo de gimnasia. Para el an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
1
0
1
Order By: Relevance
“…The articles are preferably written and cited in the English language with 96.09% of the total number of documents, which leads to thinking that there is a low level of collaboration between researchers and institutions from different countries to publish in languages other than English, such as Spanish, German, Russian, Italian, French, Ukrainian, Portuguese and Bosnian. Also, the highest scientific production is generated with research articles (81.09%) and review articles (13.65%), findings similar to that of other bibliometric studies on scientific production on collective sports (92%) (Mamani-Jilaja et al, 2023). About the analysis carried out with the VOSviewer program, in which the publications were compiled by keyword co-citations, the most used words in the study of plyometrics in sports are: human, plyometric, plyometric exercise, adult, sport, sports, and biomechanics.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The articles are preferably written and cited in the English language with 96.09% of the total number of documents, which leads to thinking that there is a low level of collaboration between researchers and institutions from different countries to publish in languages other than English, such as Spanish, German, Russian, Italian, French, Ukrainian, Portuguese and Bosnian. Also, the highest scientific production is generated with research articles (81.09%) and review articles (13.65%), findings similar to that of other bibliometric studies on scientific production on collective sports (92%) (Mamani-Jilaja et al, 2023). About the analysis carried out with the VOSviewer program, in which the publications were compiled by keyword co-citations, the most used words in the study of plyometrics in sports are: human, plyometric, plyometric exercise, adult, sport, sports, and biomechanics.…”
Section: Discussionsupporting
confidence: 85%
“…Meanwhile, the analysis of the 29 primary journals that have published research on plyometrics and its relationship with sports positions the United States, Switzerland, Italy, and the United Kingdom as the countries with the highest scientific production. This is similar to the scientific production in swimming (Orejuela Aristizabal et al, 2023) and in contrast to the scientific making in team sports, where it was found that the countries producing the most knowledge are Spain, Brazil, and the United States (Mamani-Jilaja et al, 2023).…”
Section: Discussionsupporting
confidence: 66%
“…Esto se logra a través de un análisis exhaustivo en la población, espero arrojar luz sobre este tema crucial y proporcionar información valiosa para propietarios de mascotas, profesionales de la salud animal y el público en general. (Mamani, 2022)…”
Section: Introductionunclassified
“…Despite the fact that the abundance of scientific literature on soccer tops that on any other team sport (Mamani-Jilaja et al 2023), the relationship between soccer and natural sciences has been similar to that between art and natural sciences: either superficial and conceptually redundant or serving the interests of the intellectual shareholders. As for art and science, for example, the most common forms of their integration are still those where scientific inventions embodied in the form of high technologies are used as aids in artistic projects.…”
Section: Introductionmentioning
confidence: 99%